Silicon enhanced salt tolerance by improving the root water uptake and decreasing the ion toxicity in cucumber - Wang, Shiwen; Liu, Peng; Chen, Daoqian; Yin, Lina; Li, Hongbing; Deng, Xiping (Frontiers in Plant Science, 2015)
Although the effects of silicon application on enhancing plant salt tolerance have been widely investigated, the underlying mechanism has remained unclear. In this study, seedlings of cucumber, a medium silicon accumulator plant, grown in 0.83 mM silicon solution for two weeks were exposed to 65 mM NaCl solution for another one week. The dry weight and shoot/root ratio were reduced by salt stress, but silicon application significantly alleviated these decreases. The chlorophyll concentration, net photosynthetic rate, transpiration rate and leaf water content were higher in plants treated with silicon than in untreated plants under salt stress conditions. Further investigation showed that salt stress decreased root hydraulic conductance (Lp), but that silicon application moderated this salt-induced decrease in Lp. The higher Lp in silicon-treated plants may account for the superior plant water balance. Moreover, silicon application significantly decreased Na+ concentration in the leaves while increasing K+ concentration. Simultaneously, both free and conjugated types of polyamines were maintained at high levels in silicon-treated plants, suggesting that polyamines may be involved in the ion toxicity. Our results indicate that silicon enhances the salt tolerance of cucumber through improving plant water balance by increasing the Lp and reducing Na+ content by increasing polyamine accumulation.